Optimasi Proses Pembuatan Mi Sorgum Dengan Menggunakan Ekstruder Ulir Ganda (Optimization of Sorghum Noodle Processing with Twin Screw Extruder) - Tjahja Muhandri; Subarna Subarna; Ivan Mustakim (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2013)
The objective of this research was to optimize the sorghum noodle processing with two variables i.e. extruder temperature (80, 85, 90oC) and screw speed (10, 15, 20 Hz). The optimum process was chosen by using Response Surface Methodology (RSM), based on 2 parameters, i.e. cooking loss and elongation. The result of this research showed that the optimum processing condition with desirability of 0.736, was resulted from the combination of the extruder temperature of 85oC and screw speed of 20 Hz. The verification showed that the sorghum noodles from this optimum condition had cooking loss of 11.87 %, and elongation of 234.84.  Keywords: noodle, sorghum, optimization, twin screw extruder, RSM